Studium Causa Pengangkatan Anak - Amir , Siti Aulia Hardiyanti Hasana; Saharuddin, Saharuddin; Tijjang, Bakhtiar (Jurnal Litigasi Amsir, 2021)
The adoption of a child was initially based on social interests or needs which then required arrangements for social order. This study aims to identify and understand the process of adopting a child and to identify and understand the legal consequences of adopting a child with a stipulation from the Parepare Religious Court based on decision No.31/Pdt .P/2019/Pa.Pare. This research uses normative research with a statue approach and case approach. The results showed that the adoption process at the Parepare Religious Court was based on case study No.31/Pdt.P/2019/PA.Pare based on the Compilation of Islamic Law and Government Regulation Number 54 of 2007 regarding the implementation of child adoption. In the process, some provisions must be met in the trial so that the judge can approve the adoption of the child. The legal consequence for prospective adoptive parents is that prospective adoptive parents must be fully responsible for the child to be adopted.